Broken marriage - Santos,Vilma; De Leon, Christopher; Ojeda, Orestes; Bernal, Ishmael (Regal Films, 1983)
Trapped in a world of hectic schedules, pressure, and little time for each other, Ellen and Rene decide to have a temporary separation. A marriage break-up was a serious taboo in Filipino culture in 1983. A self-discovery both for Ellen and Rene, will make you realize the value of marriage. Philippines Filipino Tagalog movie.